PERANAN WAKAF PRODUKTIF PEMUDA MUHAMMADIYAH UNTUK KESEJAHTERAAN WARGA DESA LONGKEYANG, BODEH, PEMALANG - Bahri, Amirul (IAIN Surakarta, 2016)
This study aims to examine the role of productive endowments Muhammadiyah Youth in Longkeyang, Bodeh, Pemalang. As for the issue being studied is how the first step and productive management of waqf movement Muhammadiyah Youth in Longkeyang? In addition, it will also examine how far the role of Muhammadiyah youth in productive endowments Longkeyang for the welfare of citizens. The results of this study, among others, the initial step of productive endowments movement Muhammadiyah Youth in Longkeyang namely, the anxiety of citizens and Muhammadiyah youth with a stagnant organization, so no worries